Analysis of Housing Condition and Neighbourhood Quality of Residential Core of Akure, Nigeria - Owoeye, J.O; Omole, F.K (Mediterranean Journal of Social Sciences, 2012)
The hearts of many cities in Nigeria are like island of poverty in seas of relative affluence, which does not require anyprofessional skill in environmental studies to note the difference between residential environment and the overall physical structure of thecentral parts of big cities and their suburbs. Well-designed and relatively well-maintained buildings in the suburbs and other parts ofthese cities are inhabited by the affluent, the middle-class and the privileged. But the cores are where the majority of the urbanites live,under sub-humane conditions in unkempt environments. However, the examination of some of the variables that determine urbanhousing and neighbourhood quality as it relates to the city of Akure is the major thrust of this paper. The study sampled fiveneighborhoods in the core of the city in order to examine the problems using questionnaire administration, housing demographic andfacility survey as well as physical observation as instruments for data collection. The results were analyzed with the aid of multiple linearregression models. It is observed from the research findings that poor housing system, lack of neighborhood facilities and insufficienthousehold services contribute 52.3% significant impacts to the poor quality of the environment in the cityÂ´s center. It is howeversuggested that extensive urban renewal programm in the form of provision of basic services be carried out in the area, which should besupported with improved sanitation strategies for sustainable management of the area.